2001
DOI: 10.1038/ng0501-87
|View full text |Cite
|
Sign up to set email alerts
|

A susceptibility locus for asthma-related traits on chromosome 7 revealed by genome-wide scan in a founder population

Abstract: The genetics of asthma and atopy have been difficult to determine because these diseases are genetically heterogeneous and modified by environment. The pedigrees in our study (n=86) originate in eastern central Finland (Kainuu province). According to census records, this region had only 200 households (2,000 inhabitants) in the mid sixteenth to mid seventeenth centuries. The current population of 100,000 represents the expansion of these founders within the past 400 years. Because this population is relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(118 citation statements)
references
References 21 publications
7
105
0
6
Order By: Relevance
“…We used 42 microsatellites together with 12 SNPs for chromosome 5, and 11 microsatellites with 9 SNPs for chromosome 16 placed evenly across the chromosome [18,21]. Neither of the candidate regions showed any evidence of linkage, confirming our previous observations [18].…”
Section: Linkage Analysissupporting
confidence: 83%
See 1 more Smart Citation
“…We used 42 microsatellites together with 12 SNPs for chromosome 5, and 11 microsatellites with 9 SNPs for chromosome 16 placed evenly across the chromosome [18,21]. Neither of the candidate regions showed any evidence of linkage, confirming our previous observations [18].…”
Section: Linkage Analysissupporting
confidence: 83%
“…Both chromosomes 5 and 16 were analyzed for linkage using the computer package GENEHUNTER 2.0 [26]. The SNP genotypes were combined with 42 polymorphic microsatellites for chromosome 5 and with 11 microsatellites for chromosome 16 from our genome scan [21].…”
Section: Methodsmentioning
confidence: 99%
“…Among Finnish asthma families, this locus was the only locus that reached genome wide significance level. 1 The finding was further confirmed among French-Canadian families and in another independent data set from Finland. 1 Daniels et al 2 have reported six regions of possible linkage, including 7p14-p15, and established by simulations that at least some of them are likely to be true positives.…”
Section: Introductionsupporting
confidence: 62%
“…Asthma is believed to be a complex disorder involving genetic and environmental factors, and several asthma susceptibility loci have been identified through genome-wide screening (Daniels et al 1996;Ober et al 1998;Wjst et al 1999;Dizier et al 2000;Yokouchi et al 2000;Laitinen et al 2001). Tumor necrosis factor (TNF) gene is located on chromosome 6p21 within the major histocompatibility complex class III region (Carroll et al 1987), which has been linked to asthma by several genome-wide linkage studies (Daniels et al 1996;Wjst et al 1999;Yokouchi et al 2000;Nicolae et al 2005).…”
Section: Introductionmentioning
confidence: 99%